Variabel-Variabel yang Memengaruhi Rasio P/E dan Dampaknya terhadap Return Saham (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Adam, Echan; Djumahir; Andarwati (Universitas Brawijaya, Indonesia, 2015)
This research is aimed to understand and to analyze the influence of firm size (size),DER (Debt to Equity Ratio), ROE (Return on Equity), DY (Dividend Yield), and TSB (InterestRate) on P/E Ratio (Price Earning Ratio), and also their influence on stock return. Samplingtechnique is census which results in 17 manufacture companies as the sample. Two-StageLeast Square is used to analyze data. Result of research has shown that: (1) Variables of Sizeand ROE are positively and significantly influencing P/E Ratio. Variables of DER and TSBare negatively but significantly influencing P/E Ratio; and DY is not significantly influencingP/E Ratio. (2) P/E Ratio is negatively and significantly influencing stock return. Anychanges happening with fundamental variables of finance and macroeconomic will increaseP/E Ratio in the next period, but the increase of P/E Ratio will force stock return in the nextperiod to decline.